Small Firms' Demand for Health Insurance: The Decision to Offer Insurance - Jack Hadley; James D. Reschovsky (SAGE Publishing, 2002)
This paper explores the decisions by small business establishments (<100 workers) to offer health insurance. We estimate a theoretically derived model of establishments' demand for insurance using nationally representative data from the 1997 Robert Wood Johnson Foundation Employer Health Insurance Survey and other sources. Findings show that offer decisions reflect worker demand, labor market conditions, and establishments' costs of providing coverage. Premiums have a moderate effect on offer decisions (elasticity = -.54), though very small establishments and those employing low-wage workers are more responsive. This suggests that premium subsidies to employers would be an inefficient means of increasing insurance coverage. Greater availability of public insurance and safety net care has a small negative effect on offer decisions.